Clinical implication of minimal presence of solid or micropapillary subtype in early‐stage lung adenocarcinoma. Issue 2 (24th November 2020) - Choi, Sun Ha; Jeong, Ji Yun; Lee, Shin Yup; Shin, Kyung Min; Jeong, Shin Young; Park, Tae‐In; Do, Young Woo; Lee, Eung Bae; Seok, Yangki; Lee, Won Kee; Park, Ji Eun; Park, Sunji; et al.
Abstract: Background: We investigated the clinical features and surgical outcomes of lung adenocarcinoma with minimal solid or micropapillary (S/MP) components, with a focus on stage IA. Methods: We enrolled 506 patients with lung adenocarcinoma who underwent curative resection in this study. Clinical features and surgical outcomes were compared between the groups with and without the S/MP subtype (S/MP+ and S/MP−, respectively), and between the group with an S/MP proportion of ≤5% (S/MP5) and the S/MP−. Results: The S/MP subtype was present in 247 patients (48.8%); 129 (25.5%) were grouped as the S/MP5 group. The S/MP+ and S/MP5 groups had larger tumors, higher frequency of lymph node metastasis, and more advanced stages of disease than the S/MP− group ( P  < 0.001, all comparisons). Pleural, lymphatic, and vascular invasions occurred more frequently in the S/MP+ and S/MP5 groups ( P  < 0.001, all comparisons for S/MP+ vs. S/MP−; P  ≤ 0.01, all comparisons for S/MP5 vs. S/MP−). The S/MP+ and S/MP5 groups showed a shorter time to recurrence and cancer‐related death than the S/MP− group( P  < 0.001, both comparisons). For stage I, the presence or absence of the S/MP subtype defined prognostic subgroups better than the stage IA/IB classification. Notably, in the multivariate analysis, the minimal S/MP component was a significant predictor of recurrence, even in stage IA. Conclusions: The presence of the minimal S/MP component was a significant predictor of poor prognosis after surgery, even in stage IA patients. Clinical trials to evaluate the advantages of adjuvant chemotherapy for this subset of patients and further investigations to understand underlying biological mechanisms of poor prognosis are needed. Key points: Significant findings of the study: We demonstrated that only minimal presence of solid or micropapillary component was profoundly associated with aggressive clinicopathological features and poor prognosis after complete resection even in stage IA lung adenocarcinoma. What this study adds: Our results suggest that minimal presence of these subtypes is a strong prognostic factor which should be taken into account in the risk assessment for adjuvant chemotherapy in lung adenocarcinoma. Abstract : We demonstrated that only minimal presence of solid or micropapillary component was profoundly associated with aggressive clinicopathological features and poor prognosis after complete resection even in stage IA lung adenocarcinoma. Our results suggest that minimal presence of these subtypes is a strong prognostic factor which should be taken into account in the risk assessment for adjuvant chemotherapy in lung adenocarcinoma.